AKU SENI BISA HITUNG: PELATIHAN AKUNTANSI KREATIF DAN MANAJEMEN KEUANGAN UNTUK GURU DAN SISWA SEKOLAH MENENGAH - Ihyani, Layali; Komala, Rina; Wangi, Baiq Larre Ginggit Sekar; Marlina, Febria Nurmelia; Marswandi, Ega Dwi Putri; Saputra, Sahdan (CV Sentra Nusa Connection, 2025)
This training program aims to enhance accounting understanding and financial literacy through a creative, art-based approach for secondary school teachers and students. The implementation method consists of three phases: (1) an initial needs assessment survey and coordination with schools, (2) development of interactive modules based on financial storytelling, game simulations, and visualizations, and (3) a four-week training program featuring three main sessions (basic accounting, personal financial management, and innovative teaching workshops). Evaluation results indicate a significant improvement in participants’ understanding (students' average post-test score increased to 78 from 45; teachers' score rose to 82 from 58) along with high active participation at a rate of 95%. Key findings demonstrate that creative methods such as games, artistic analogies, and mini projects are effective in making financial concepts more understandable and applicable. The program recommends developing digital modules, integrating them into the school curriculum, and conducting follow-up training to broaden its impact. This training not only enhances financial competence but also paves the way for the development of innovative accounting learning models in educational environments.